2019
DOI: 10.1103/physrevb.100.195423
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport of a spin-orbit-coupled Luttinger liquid

Abstract: The charge transport of a (Tomonaga-)Luttinger liquid with tunnel barriers exhibits universal scaling: the current-voltage curves measured at various temperatures collapse into a single curve upon rescaling. The exponent characterizing this single curve can be used to extract the strength of electron-electron interaction. Motivated by a recent experiment on InAs nanowires [Sato et al., Phys. Rev. B 99, 155304 (2019)], we theoretically investigate the analogous behavior of a spin-orbit-coupled Luttinger liquid.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 78 publications
2
23
0
Order By: Relevance
“…Second, while the 2PB process from both a local impurity and quenched disorder result in similar power-law resistance, they differ in the crossover value of the interaction parameter below which the channel becomes insulating, namely K < 1/4 and K < 3/8, respectively. This difference, arising from the different scaling dimensions of the corresponding operators, has been pointed out in the context of nonhelical channels (Giamarchi 2003, Hsu, Stano, Sato, Matsuo, Tarucha & Loss 2019. Generally speaking, the additional time integral in the disorder-averaged effective action [see (98a)] makes the backscattering due to quenched disorder more RG relevant than the one due to a single impurity.…”
Section: Generic Helical Tomonaga-luttinger Liquidmentioning
confidence: 99%
See 2 more Smart Citations

Helical Liquids in Semiconductors

Hsu,
Stano,
Klinovaja
et al. 2021
Preprint
Self Cite
“…Second, while the 2PB process from both a local impurity and quenched disorder result in similar power-law resistance, they differ in the crossover value of the interaction parameter below which the channel becomes insulating, namely K < 1/4 and K < 3/8, respectively. This difference, arising from the different scaling dimensions of the corresponding operators, has been pointed out in the context of nonhelical channels (Giamarchi 2003, Hsu, Stano, Sato, Matsuo, Tarucha & Loss 2019. Generally speaking, the additional time integral in the disorder-averaged effective action [see (98a)] makes the backscattering due to quenched disorder more RG relevant than the one due to a single impurity.…”
Section: Generic Helical Tomonaga-luttinger Liquidmentioning
confidence: 99%
“…First, for a clean hTLL that is free from backscattering and adiabatically connected to Fermi-liquid leads, it was found that the dc conductance of the helical channel does not depend on K (Hsu et al 2018a), resembling the ballistic conductance in a nonhelical channel (Maslov & Stone 1995, Ponomarenko 1995, Safi & Schulz 1995. Second, while in the presence of backscattering sources the conductance through a helical channel in general depends on the interaction strength, knowledge of the backscattering mechanism and resistance sources is required to extract K. This complication makes the extraction of the experimental K value highly nontrivial, as pointed out by (Väyrynen et al 2016, Hsu et al 2017, Hsu, Stano, Sato, Matsuo, Tarucha & Loss 2019.…”
Section: Interacting Helical Channels: Helical Tomonaga-luttinger Liquidmentioning
confidence: 99%
See 1 more Smart Citation

Helical Liquids in Semiconductors

Hsu,
Stano,
Klinovaja
et al. 2021
Preprint
Self Cite
“…Spin-orbit coupling (SOC) in these systems plays an important role on the realization of spintronic devices [28,29]. Thus, an interplay of (large) SOC and (large) e-e interactions in the TLL regime is an interesting question and has gained both theoretical and experimental attention in recent years [30][31][32]. Impurity effects in conventional TLLs with decoupled channels were studied in the original works [12,13], and can be summarized by phase portrait at T = 0, presented in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of the phase portrait in the presence of SCC has not yet been considered, although there are several studies which partially addressed this question in different aspects [34,35]. Particularly, impurity effects on transport properties in the case of the SCC caused by SOC were recently studied [31,32]. As our main motivation of this work we consider modification of the phase portrait in the presence of SOC.…”
Section: Introductionmentioning
confidence: 99%